KARAKTERISTIK ARANG AKTIF TANDAN KOSONG KELAPA SAWIT YANG DIIMPREGNASI LOGAM NIKEL SEBAGAI KATALIS - Rina Novia Yanti (Jurnal Penelitian Hasil Hutan, 2020)
Activated charcoal from biomass can be used for various applications because its high porosity. One of the utilizationfor activated charcoal as catalyst raw material from empty palm oil bunches. This study aimed to determine thecharacteristics of activated charcoal with nickel (Ni) impregnation as catalyst raw material in the upgrading bio-oil.Activated charcoal used 10%, 15%, and 20% H3PO4was immersed for 24 hours, and calcinated at temperatureof 750°C with steam activation time for 60 minutes. The optimum of the manufacturing of activated charcoal withwith 10% H3PO4, then impregnated with nickel in various concentration: 1%, 2%, and 3%. Results showed thecharacteristic of nickel impregnated activated charcoal were as follows: iodine absorbance capacity 554–756 mg/g,methylene blue absorbance capacity 38–90 mg/g, surfaces area 96–218 m2/g and pore diameter of 8.48–16.21micron meter.